Evaluation of the Funeral Aid Social Assistance Policy of the Social Service Office of North Minahasa Regency - Tuwaidan, Marcel J.; Bogar, Wilson; Wawointana, Thelma (JR Education, 2025)
This study evaluates the implementation of the Funeral Assistance Social Aid policy enacted the regional government has an imperative to provide social protection for underprivileged communities experiencing the bereavement of a family member. Through North Minahasa Regent Regulation No. 27 of 2021, the North Minahasa Regency Government established a funeral assistance grant of IDR 3,000,000 to alleviate the financial burden on surviving family members. However, in its implementation, this policy has encountered several administrative, technical, and geographical challenges that affect the effectiveness of benefit distribution. The purpose of this study is to evaluate the implementation of the Funeral Assistance Social Aid policy and to identify the obstacles arising during its delivery, as well as to offer policy recommendations for improving the efficiency and effectiveness of aid distribution. This research employs a qualitative approach, collecting data through in-depth interviews, observation, and document review. Informants include officials from the Social Service Office, village administrators, community leaders, and aid recipients. Data analysis follows the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. Findings indicate that the funeral assistance program is considered quite effective by the community in easing the economic burden during mourning. Distribution processes are relatively swift (3–7 working days) when documentation is complete, and recipients report substantial benefit from the aid. Nevertheless, challenges persist, including incomplete documentation, limited internet connectivity in remote areas, inter-agency coordination delays, and insufficient public outreach. Despite these constraints, the Social Service Office has introduced innovations such as training for village officers and using the OSS-Duka system to expedite data verification. Based on these findings, it can be concluded that the Funeral Assistance Social Aid policy has positively impacted recipients. However, its effectiveness can be further enhanced through simplification of procedures, capacity building at the village level, and improvements to the digital service system. The recommendations arising from this study are expected to strengthen a more responsive and equitable social protection framework in North Minahasa Regency.